An analysis of travel mode transfer and first-and last-mile trips of public transport users in Bangkok - Rattanan Hempholchom; Kunnawee Kanitpong; Ampol Karoonsoontawong; Bhatt, Ayushman; Hadikusumo, Bonaventura H.W.; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
This study focuses on identifying the key factors that influence individuals{u2019} mode choices for First and Last Mile (FLM) travel connected to BTS stations in Bangkok. It also looks at how household situations, like family size or vehicle ownership, influence these travel decisions. The study also offers suggestions to encourage people to use more environmentally friendly ways of getting to the BTS, like walking or using public transport. Data were gathered through a questionnaire survey involving 1,216 BTS passengers, resulting in a total of 2,293 recorded FLM trips. The analysis was conducted using three different models: the Multinomial Logit (MNL), Nested Logit (NL), and Latent Class (LC) models. However, the NL model did not perform well due to invalid nesting, and the LC model could not produce reliable results. As a result, the MNL model was used as the main tool for analysis. Among all versions of the MNL model tested, Model 19 showed the best performance. It included variables related to travel time, cost, distance, demographic characteristics, household structure, and built environment factors. The results show that cost and time sensitivity, accessibility, vehicle ownership, and household size all significantly affect FLM mode choice. Based on these findings, several recommendations were made. These include improving pedestrian access and cycling paths near BTS stations, enhancing bus services, and encouraging the use of shared electric vehicles. The study also suggests that future research could expand the study area or explore other rail systems, such as the MRT Blue Line.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Transportation Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 2025
Keywords: Urban transportation -- Thailand -- Bangkok; Choice of transportation -- Thailand -- Bangkok